(untitled) (Bangladesh Journal of Agricultural Research, 2013)
A study was undertaken to evaluate effectiveness of foliar spray with 33 plant extracts against leaf spot (Tikka) of groundnut caused by Cercospora arachidicola and Cercosporidium personatum. Bavistin and BAU-Biofungicide were included in the experiment as checks and spray of plain water represented control. Almost all treatments gave considerable reduction in disease incidence and increase in growth parameters, pod and haulm yield compared to control. The most effective materials were Bavistin 50 WP, BAU-Biofungicide, leaf extract of neem, tomato, datura black, and datura white. The materials decreased spot number per leaf, defoliation per plant, incidence of leaf spot, and number of infected leaf per plant by 35.45 -60.07, 42.06-72.20, 51.9763.58, and 38.33 to 46.89 % and increased pod yield and haulm yield by 64.37-111.41 and 32.35- 74.71 %, respectively. The materials may be recommended against the disease after economic analysis. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16976 Bangladesh J. Agril. Res. 38(3): 491-503, September 2013